Breakdown Time Analysis in The Effort to Maximize Medical Equipment Productivity in Hospital - Buyung Sakti Hamel (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Health equipment in hospitals determines the productivity of health service delivery. Medical equipment must continue to function properly. One way to measure the success of maintaining medical devices is by standard Breakdown Time. This study aims to determine the application of standard Breakdown Time on damaged medical devices. The research method used is a descriptive qualitative method with in-depth interviews. There are interviewees with private status and ASN (government employees). From the private sector, there are consultants, technical managers, and administrators of professional organizations in the field of medical equipment. Interviewees with ASN status are practitioners of maintenance and repair of health equipment in government hospitals. The results of the interviews were compiled into 6 groups based on the main questions asked, then analyses descriptively. The results of the study, Standard Breakdown Time have not been applied comprehensively in hospitals. Several informants informed that although there is an application of breakdown time, the standard is not yet clear and is only applied to high-tech equipment and/or for a minimal number of equipment there is only one in the hospital. For other equipment, there is no standard when the damage occurs, until when the damaged equipment must be able to function again. In conclusion, the Standard Breakdown Time for medical devices is important and its application must be supported by Ministerial-level regulations.